On the Use of a Confined Sand Cell to Dampen Induced Machine Vibration in a Stabilized Clay Numerical Study - Kassem, Engy M.; Azzam, Waseim; Elsiragy, Mohamed (Civil Engineering Journal, 2025)
Environmental vibrations produced often by industrial and construction processes can affect adjacent soils and structures, sometimes resulting in foundation failure and structural damage. The application of confined cells under foundations as a mitigation technique against dynamic sources, such as generators, is investigated in this study. Numerical models were developed using Plaxis 3D software to simulate the effect of a vibrating source on a circular footing, both with and without confined cells filled with sand soil at varying depths and diameters. In these cells, the soil modeling considered compaction loads typical in actual construction conditions. Results indicate that placing a minimum-diameter cell closer to the foundation with adequate penetration depth can significantly enhance dynamic response and reduce subgrade deformation. The effectiveness of confined soil in minimizing displacement amplitude in the foundation is evaluated, revealing an impressive 86% reduction with specific cell dimensions (Hc/D = 0.50 and Dc/D = 1.15). Moreover, peak particle velocity and excess pore water pressure at monitored points in the surrounding environment experience reductions of 62% and 87%, respectively, demonstrating substantial vibration attenuation. The study does effectively highlight the novelty of the confined sand cell approach, positioning it as a more targeted, efficient, and cost-effective alternative to existing methods, especially for conditions where large-scale, deep vibrations are a concern. Doi: 10.28991/CEJ-2025-011-01-018 Full Text: PDF